Rattan, rubber, or oil palm: cultural and financial considerations for farmers in Kalimantan - Belcher, B.; Rujehan; Imang, N.; Achdiawan, R. (2004)
Forest-based farmers are faced with rapidly changing economic opportunities due to many factors. In response, farmers are changing their main economic activities and land uses. This study compares the financial costs and benefits of the principal land use options in two sub-districts of East Kalimantan Province, Indonesia. Financial benefits of oil palm plantation, traditional rattan gardens, intensive rubber plantation, and traditional rubber plantation are compared on a land unit basis. Oil palm is by far the most profitable, followed by rattan gardens. Rubber production, at current prices, is not profitable. Benefit-cost ratios and returns to labor, which better reflect the farmer perspective, reveal that rattan is more attractive, with oil palm in a strong second place. Non-financial considerations also help to explain the resilience of the rattan garden system. The conclusions summarize the findings and offer options to counter the strong negative impact of recent events on the rattan farmers.